Effect of free air ball (FAB) formation on wire bond integrity in palladium coated copper (PdCu) wire / Mohd Firdaus Manap - Mohd Firdaus , Manap (2017)
The free air ball (FAB) formation during wire bond process of fine diameter palladium coated copper (PdCu) wire and bare copper wire were observed. The formation of FAB is studied by using FAB measurement method with different shielding gas types and gas flow rates as input parameters. The effect of each input parameters to the FAB formation was studied and as a result the gas flow rate window without deformation of FAB were obtained. It was observed bare copper wire having smaller window parameter in order to form proper FAB compared to PdCu wire which concludes due to inhomogeneous oxidation effect. Meanwhile, from the measurement, it was observed that the value of HFAB is higher when pointed FAB occurred but lower when the FAB formation having off center shape. Further study was performed on the bondability and reliability aspect of the bonded ball from the FAB formation results. Combination of PdCu wire with forming gas shows higher ball shear and intermetallic coverage (IMC) at T0 and after bake compared to bare copper. It also shows PdCu wire having zero failure after reliability test and no IMC separation observed which indicate better reliability performance compared to bare copper wire.